2021
DOI: 10.1007/s10815-021-02314-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel posttranslational modification of histone, H3 S-sulfhydration, is down-regulated in asthenozoospermic sperm

Abstract: Oxidative stress is one of the major causes leading to male infertility including asthenozoospermia. Hydrogen sulfide (H2S) has been widely recognized to be a potent antioxidant whose role is partially implemented by protein S-sulfhydration. However, protein S-sulfhydration has not been reported in germ cells. Therefore, we investigated whether asthenozoospermia could be associated with sperm protein S-sulfhydration. S-sulfhydrated proteins in human sperm were enriched via biotin-switch assay and analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In this regard, a series of studies have demonstrated that H 2 S has important physiological and cytoprotective functions in the biological systems 39 , 40 . Some studies have revealed some mechanisms for the regulatory effect of H 2 S on ROS production in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a series of studies have demonstrated that H 2 S has important physiological and cytoprotective functions in the biological systems 39 , 40 . Some studies have revealed some mechanisms for the regulatory effect of H 2 S on ROS production in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is necessary to focus our attention on sperm motile capacity, and the abnormal content or presence of PTMs, such as the reduced abundance of lysine glutarylation in several proteins located in the tail of human spermatozoa, just as a diminished quantity of S-sulfhydrated H3 and H3.3 histones positively correlate with sperm progressive motility [12,13]; conversely the level of SUMO1-positive spermatozoa and the quantity of lysine 2-hydroxyisobutyrylation in sperm proteins trend towards higher grades in asthenozoospermic men compared with normozoospermic ones, indicating a negative association with the motility of human spermatozoa in this case [14,15]. Additionally, lysine acetylation seems to be essential for human sperm motility and fertilization [16].…”
Section: Introductionmentioning
confidence: 99%